Al-Tawatturāt bayn al-Sunnah wa al-Shī'ah fī Maluku al-Shamālīyah: Durūs min al-Māḍī - Muhammad Amin Nurdin; Herdi Sahrasad; Smith Alhadar (Studia Islamika, 2020)
This article explains the conflict between the majority of Sunni Muslims and the minority Shia in Ternate from 2012 until 2018. At the start, the Sunni Muslims in Ternate complained about the existence of a Shia sect community of around dozens of people in Jerbes and Marikrubu villages of North Ternate regency which has caused unrest for the community. Concerned with the spread of this so-called heresy, on January 25, 2012, the Sunni Muslim community carried out the expulsion of the Shiite settlers in the village. Shia's followers from Jerbes village were secured by the security forces to avoid undesirable happenings. Indeed, this doesn't need to happen if both Sunni and Shia Muslims in Ternate realized that they have local wisdom and legacy of traditional values and virtue, from which Islam and local genius values could put forward a peaceful solution and common platform so that harmony, concord, stability, and peace can be maintained by all parties.